β-Hydroxybutyrate in Cardiovascular Diseases : A Minor Metabolite of Great Expectations - Wei, Shao; Binbin, Liu; Yuan, Wu; Zhong, Zhang; Donghai, Lin; Caihua, Huang (Frontiers in Molecular Biosciences, 2022)
Despite recent advances in therapies, cardiovascular diseases ( CVDs ) are still the leading cause of mortality worldwide. Previous studies have shown that metabolic perturbations in cardiac energy metabolism are closely associated with the progression of CVDs. As expected, metabolic interventions can be applied to alleviate metabolic impairments and, therefore, can be used to develop therapeutic strategies for CVDs. β-hydroxybutyrate (β-HB) was once known to be a harmful and toxic metabolite leading to ketoacidosis in diabetes. However, the minor metabolite is increasingly recognized as a multifunctional molecular marker in CVDs. Although the protective role of β-HB in cardiovascular disease is controversial, increasing evidence from experimental and clinical research has shown that β-HB can be a “super fuel” and a signaling metabolite with beneficial effects on vascular and cardiac dysfunction. The tremendous potential of β-HB in the treatment of CVDs has attracted many interests of researchers. This study reviews the research progress of β-HB in CVDs and aims to provide a theoretical basis for exploiting the potential of β-HB in cardiovascular therapies.